ÙƒÙŠÙ Ù†ÙÙ‡Ù… Ø§Ù„Ø¯ÙŠÙ†ØŸ - Mohammed, Dheen (DINIKA : Academic Journal of Islamic Studies, 2017)
This paper attempts to present the concept of religion as articulated by Muslim scholars contributing thus to the ongoing current debate on understanding religion. The need for the paper arises from the factual position that western perceptions about approaches to religion have inundated the Muslim world (and the world at large) to the extent that the intellectual endeavors of many Muslim academics are largely shaped by these perceptions while the Muslim contribution in this regards is minimal if not significantly absent from the scene. This paper endeavors to situate the Muslim perception of understanding other religions within the context of the general framework.Â Keywords:Religion, Concept of Religion, Approaches to Religion